ENGLISH PEDAGOGY THROUGH HOLISTIC APPROACH FOR EFL STUDENTS’ ENGAGEMENT IN INDONESIA - Tahir, Ismail (PEOPLE: International Journal of Social Sciences, 2017)
Holistic approach has been considered as the approach in teaching and learning process. The purpose of this study was to investigate an English pedagogy using holistic approach for Indonesian students. The study also aimed at exploring students’ engagement when learning English. Importantly, engaging students is really needed for Indonesian students as English Foreign Language (EFL) learners in order to build up their motivation to learn English. Moreover, as the conceptual paper, this study used the description procedure in exploring and enriching the development of the explanation of this paper. This paper investigated how much the use of holistic approach helped Indonesian EFL students explore their engagement. The description explained that EFL students intend to have this kind approach to be engaged by their teacher. Further, this framework also may have pedagogical implications for the fields of teachers and students feedback, the study ended with some recommendation to assist and direct the future research.